Risk assessment of the human factor in ‘staff - hoists - production environment’ system at machine-building enterprises - Elena Vladimirovna Yegelskaya; Anatoly Arkadyevich Korotkiy (Advanced Engineering Research)
The research objective is to develop the technique of assessing a human factor risk in the ‘staff - hoists - production environment’ system. The proposed method allows evaluating the degree of staff training and of the appropriate managerial solutions at the machine-building enterprises operating hoists. Three groups of hazards associated, respectively, with the false staff operation, the hoist state, and the production environment of the machine builder, are considered. An interpretation of the potential adverse event instance (misfortune, incident, accident) is presented. Based on the analysis of the accident investigation reports at the machine-building enterprises operating hoists and on the conducted questionnaire surveys, the specific dangerous actions of the staff and executive officers (managers and expert personnel) are identified and classified. As a result, the matrix is constructed to determine the probability of potential accidents, incidents or misfortunes depending on the frequency of the false staff actions. The study allows drawing the following conclusion. At the machine-building enterprises of the 4th hazard class, it is considered expedient to apply the expert analysis method to assess the organizational human error causes when running the plants with hoists. Under these conditions, the method of risk assessment appears quite simple and effective in terms of the engineering safety analysis.